GDNF enhances human blood-nerve barrier function in vitro via MAPK signaling pathways. Issue 4 (2nd October 2018) - Dong, Chaoling; Ubogu, Eroboghene E.
ABSTRACT: The human blood-nerve barrier (BNB) formed by endoneurial microvascular endothelial cells, serves to maintain the internal microenvironment in peripheral nerves required for normal axonal signal transduction to and from the central nervous system. The mechanisms of human BNB formation in health and disease are not fully elucidated. Prior work established a sufficient role for glial-derived neurotrophic factor (GDNF) in enhancing human BNB biophysical properties following serum withdrawal in vitro via RET-tyrosine kinase-dependent cytoskeletal remodeling. The objective of the study was to ascertain the downstream signaling pathway involved in this process and more comprehensively determine the molecular changes that may occur at human BNB intercellular junctions under the influence of GDNF. Proteomic studies suggested expression of several mitogen-activated protein kinases (MAPKs) in confluent GDNF-treated endoneurial endothelial cells following serum withdrawal. Using electric cell-substrate impedance sensing to continuously measure transendothelial electrical resistance and static transwell solute permeability assays with fluoresceinated small and large molecules to evaluate BNB biophysical function, we determined MAPK signaling was essential for GDNF-mediated BNB TEER increase following serum withdrawal downstream of RET-tyrosine kinase signaling that persisted for up to 48 hours in vitro . This increase was associated with reduced solute permeability to fluoresceinated sodium and high molecular weight dextran. Specific GDNF-mediated alterations were detected in cytoskeletal and intercellular junctional complex molecular transcripts and proteins relative to basal conditions without exogenous GDNF. This work provides novel insights into the molecular determinants and mechanisms responsible for specialized restrictive human BNB formation in health and disease.